Meta-analysis for assessing the healing process of ulcers among diabetic patients: Cases of HbA1c, lipid, S. Creatinine, Adiponectin, Cat D, HSP70, HSP47, 25-hydroxy vitamin D. Issue 1 (January 2019) - Zubair, Mohammad; Ahmad, Jamal
Abstract: Background: The study aims to investigate the significance of predictors including HbA1c, Lipid, S. Creatinine, Adiponectin, Cat D, HSP70, HSP47, and 25-hydroxy vitamin D and to evaluate the rate of healing of ulcers among the diabetic foot patients. Methods: A retrospective method is used to quantitatively assess the role of HbA1c, Lipid, S. Creatinine, Adiponectin, Cat D, HSP70, HSP47, and 25-hydroxy vitamin D in the healing process of ulcer among diabetic patients. A total of 192 diabetic patients were included, who underwent ulcer healing diagnosis. Results: The results have shown a positive and significant correlation between Adiponectin and Cat D with group 2. The findings have shown higher prevalence of Cad D among patients with group 1, HSP70 among patients with group 2, HSP47 among patients with group 2, and 25-hydroxy vitamin D among patients with group 1. Conclusion: The study concluded that insignificant predictors should be assessed more comprehensively to reveal its efficacy on healing of ulcers with different grades.